Factors Affecting the Perceived Effectiveness in Preventing the Transmission of COVID-19 in Indonesia: Integrating the Extended Theory of Planned Behavior and Health Belief Model - Dino Caesaron; Yunita Nugrahaini Safrudin; Sheila Amalia Salma; Tiara Verita Yastica; Afin Rizqi Pramadya (Bina Nusantara University, 2021)
The coronavirus (COVID-19) is an infectious disease declared a pandemic worldwide by the World Health Organization (WHO). The purpose of the research was to look at the factors in public health behavior that affected the effectiveness of preventing the transmission of the COVID-19 based on the extended Theory of Planned Behavior (TPB) and Health Belief Model (HBM). The research was a correlational study. The research applied a purposive sampling method, with 483 respondents coming from various islands in Indonesia. Based on the analysis using Partial Least Square-Structural Equation Modelling (PLS-SEM), TPB factors like individuals' behavioral intention to follow COVID-19 preventive measures are significantly affected by subjective norm and perceived behavior control. On the other hand, personal attitude does not significantly affect an individual's behavioral intention to follow COVID-19 prevention steps. HBM shows an individual’s behavior intention to follow the COVID-19 preventive measures is significant and directly affected by perceived severity, perceived barrier, perceived self-efficacy, and cues to action. Meanwhile, the perceived susceptibility and perceived benefits do not significantly and directly influence an individual's behavioral intention to follow the COVID-19 preventive measures. The findings from the research can be used to evaluate the effectiveness in several countries in facing the COVID-19 pandemic.